Determination of Chloride Ion (Cl-) Conditions In Dog Well Water In Kecamatan Kaliwungu, Kendal Using Mohr Argentometry Method: Penentuan Kadar Ion Klorida (Cl-) Pada Sampel Air Sumur Gali di Kecamatan Kaliwungu, Kendal Menggunakan Metode Argentometri Mohr - Anggi Mukromin; Yari Mukti Wibowo (Jurnal Kimia dan Rekayasa, 2023)
Coastal areas are areas that often experience difficulties in obtaining clean water. In this coastal area sea water intrusion often occurs, so that the chloride content in fresh water is high. Researchers wanted to determine the levels of chloride ions in samples of dug well water in the Kaliwungu District, Kendal Regency. This research was conducted using the Argentometry Mohr titration method. The sample population obtained is 6 from different points, where each sample has a coordinate point. Determination of the distance between the coordinates of each of the wells to the coastal area or ponds is taken from 4 directions, then the closest distance is taken. The research results obtained chloride levels from 6 well water samples S1, S2, S3, S4, S5, S6 in units of mg/L respectively: 74.28; 106.63; 102.15; 127.03; 112.60 and 72.62. The results of the study stated that the well water samples closest to the coast had the highest levels of chloride ions. This is possible because of the large amount of seawater seeping into the dug well water. Based on the Regulation of the Minister of Health of the Republic of Indonesia Number 492/Menkes/Per/IV/2010 the maximum limit for chloride ions for drinking water is 250 mg/L. The levels of the samples from the six wells obtained met the predetermined requirements, so it can be concluded that the 6 well water samples had good quality, when viewed from their chloride ion levels. AbstrakDaerah pesisir pantai merupakan salah satu daerah yang sering mengalami kesulitan untuk memperoleh air bersih. Pada daerah pesisir pantai ini sering terjadi intrusi air laut, sehingga kadar klorida dalam air tawarnya tinggi. Peneliti ingin menentukan kadar ion klorida pada sampel air sumur gali di daerah Kecamatan Kaliwungu Kabupaten Kendal. Penelitian ini dilakukan dengan menggunakan metode titrasi Argentometri Mohr. Populasi sampel yang didapatkan berjumlah 6 dari titik berbeda, dimana masing-masing sampel memiliki titik koordinat. Penentuan jarak antara titik koordinat dari masing-masing dari masing-masing sumur terhadap wilayah pesisir atau tambak diambil dari 4 arah, kemudian diambil jarak yang terdekat. Hasil penelitian diperoleh kadar klorida dari 6 sampel air sumur S1, S2, S3, S4, S5, S6 dalam satuan mg/L berturut-turut sebesar : 74,28; 106,63; 102,15; 127,03; 112,60 dan 72,62. Hasil penelitian menyatakan bahwa sampel air sumur yang paling dekat dengan pesisir pantai mempunyai kadar ion klorida paling besar. Hal ini dimungkinkan karena banyaknya air laut yang merembes masuk ke air sumur gali. Berdasarkan Peraturan Menteri Kesehatan Republik Indonesia Nomor 492/Menkes/Per/IV/2010 batasan paling banyak ion klorida untuk air minum sebesar 250 mg/L. Kadar sampel dari keenam sumur yang diperoleh memenuhi syarat yang telah ditetapkan, sehingga dapat disimpulkan bahwa 6 sampel air sumur mempunyai kualitas yang baik, jika dilihat dari kadar ion kloridanya.